2015
DOI: 10.1016/j.epsl.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Transport and reaction of iron and iron stable isotopes in glacial meltwaters on Svalbard near Kongsfjorden: From rivers to estuary to ocean

Abstract: Glacial meltwater has been suggested as a significant source of potentially bioavailable iron to the oceans. However, the supply of dissolved iron (dFe) in glacial meltwaters is poorly constrained as few sites have been studied, and because the chemical processing of Fe during transport from glaciers to the adjacent coastal ocean is not well understood. In order to better constrain glacial fluxes of dFe to the ocean, iron concentrations, iron stable isotopes (δ 56 Fe), and other supporting chemical and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
81
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 72 publications
(98 reference statements)
15
81
3
Order By: Relevance
“…2), a feature that is also observed in glacially fed rivers such as the Copper River in Alaska Escoube et al, 2015). This observation agrees with previous d 56 Fe measurements in glacial outflow from Bayelva River near Kongsfjorden Svalbard (500 m downstream of the terminus; (Zhang et al, 2015). The measured d…”
Section: Subglacial Streams As Indicators Of Chemical and Physical Wesupporting
confidence: 81%
See 2 more Smart Citations
“…2), a feature that is also observed in glacially fed rivers such as the Copper River in Alaska Escoube et al, 2015). This observation agrees with previous d 56 Fe measurements in glacial outflow from Bayelva River near Kongsfjorden Svalbard (500 m downstream of the terminus; (Zhang et al, 2015). The measured d…”
Section: Subglacial Streams As Indicators Of Chemical and Physical Wesupporting
confidence: 81%
“…As has been demonstrated for other Fe sources to the North Atlantic (Conway and John, 2014;Zhang et al, 2015), constraining the Fe isotopic composition of glacial melt waters (expressed as d 56 Fe or d 57 Fe in the literature) may facilitate the tracing of glacial Fe in proximal oceans. Such constraints are not straightforward to obtain, as there is reason to suspect that the Fe isotopic composition of subglacial streams may vary considerably.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the size fractions used to define Fe phases vary between studies, our concentrations are within the range reported for freshwater elsewhere around Greenland (Statham et al, 2008;Bhatia et al, 2013b;Hawkings et al, 2014). The non-conservative decline in DFe along estuaries has been well characterized for many river systems worldwide (Boyle et al, 1977;Sholkovitz, 1978), including some in glaciated catchments (Schroth et al, 2014;Zhang et al, 2015). The dominant feature of DFe and TdFe distribution in this fjord however appears to be the particle plume by GF11 which causes some deviation from the expected decline in DFe concentration with increasing salinity (Figure 7).…”
Section: Particles and Fesupporting
confidence: 70%
“…Fe behavior in the glacially fed Arctic River Bayelva supports this hypothesis. Eighty percent of dissolved Fe (<0.40 µm) was found to aggregate along a 4 km stretch of river prior to additional removal during estuarine mixing (Zhang et al, 2015). This resulted in a final dissolved Fe removal of around 98% between a glacial outflow and the sea, which is at the upper end of the range observed in temperate estuarine systems (Boyle et al, 1977;Sholkovitz, 1978).…”
Section: Fe Input and Potential Export To Coastal Seasmentioning
confidence: 99%